Novel Method for Laryngotracheal Reconstruction: Combining Single- and Double-Stage Techniques. (July 2013) - Setlur, Jennifer; Maturo, Stephen; Hartnick, Christopher J.
Objectives: Traditional open techniques for laryngotracheal reconstruction are either single- or double-stage procedures. Some patients may benefit from the presence of a long, single-tube stent, such as an endotracheal tube, but their predicted need for a 2-stage procedure and a persistent tracheostomy is high. We describe a novel technique for airway reconstruction that combines the methods of both single- and double-stage procedures. Methods: We present a retrospective review of 4 patients. All patients underwent laryngotracheal reconstruction by a single surgeon. After the operation, the airway was stented with nasotracheal intubation. A small stent, fashioned from an endotracheal tube, was placed in the tracheostoma to keep it patent. The patients subsequently underwent extubation and replacement of the tracheostomy tube. Results: The study included 1 patient with grade 4 subglottic stenosis, 2 patients with grade 3 subglottic stenosis, and 1 patient with a posterior glottic scar. All were tracheostomy tube-dependent. Serial bronchoscopy was used to follow the patients for a minimum of 9 months after the operation. All 4 patients have since met the criteria for decannulation. Conclusions: This hybrid reconstruction merges the advantages of both the single- and double-stage procedures. It adds versatility to the surgical toolbox for airway reconstruction.